THEMATIC CHARACTER BASED LEARNING IN PRIMARY SCHOOL - Osco Parmonangan Sijabat (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2019)
This study aims to find a design study model character education consists of learning tools and study guides students on thematic learning. The method used is research and development (Research and Development) combined with action research methods.The survey results revealed that students are given guidance at the time of the trial in the class did not give meaningfulness in learning. On the Character Education Model Integrated Thematic Teaching at primary schools HKBP Pematangsiantar developed through this research feasible tested again on the stage of a pilot project to test subjects' primary schools HKBP Pematangsiantar grade 2 and 3. Then proceed to the stage of dissemination in the 1st grade, primary school HKBP Pematangsiantar so that it can serve as the basis for the submission of policy proposals in the field of character education.